Η ενδιάμεση τεκτονομεταμορφική ζώνη των Ελληνίδων - Παπανικολάου, Δ. (Δελτίο Ελληνικής Γεωλογικής Εταιρείας, 1988)
The structure and geotectonic evolution of the medial tectonometamorphic belt is described. The main tectonic units are classified to parts of continental plates and of oceanic plates. A younger age of tectonism (Late Eocene) is detected at the base than at the top (Early Cretaceous) of the belt. The tectonic evolution of the belt includes two convergent zones of plate movement, one during Late Jurassic-Early Cretaceous between the Serbomacedonian and the Pelagonian microcontinents with obduction of the Axios oceanic lithosphere onto the Pelagonian giving rise to the Internal Hellenides and another during Late Cretaceous-Eocene that included a subduction zone with blueschists generation and a subsequent collision of the microcontinents of the Pelagonian and the Lydo-Karian (Menderes), giving rise to the External Hellenides. Since Miocene times the previous paleogeographic-geotectonic units were consolidated to an unique structure.
Keywords: Hellenides, Cyclades, Pelagonian